Chronic Q fever: A missed prosthetic valve endocarditis possibly for years - Ferraz, Rita Veiga (IDCases, 2016)
Chronic Coxiella burnetii endocarditis usually develops in people with underlying heart disease and accounts for 60–70% of chronic Q fever. Onset is generally insidious and manifestations are atypical. The authors report a case of Coxiella burnetii prosthetic valve endocarditis in a 53 years- old patient with recurrent mechanical valve dehiscence on mitral position. He lived in a rural area with sheep and goats on the surroundings. During a 9 year- period, he was submitted to three cardiac mitral valve surgeries two of which with no Q fever diagnosis suspicion. Diagnosis was based on a positive serology test (Indirect imunofluorescence). Treatment consisted in a combination of prolonged course of hydroxychloroquine plus doxycycline and surgical replacement of the mitral valve, with a favorable outcome. With this case report, the authors pretend to highlight the not always expected diagnosis of Q fever endocarditis. If not considered, Coxiella burnetii endocarditis may lead to multiple cardiac surgeries, greater morbidity and potentially death.